A RESISTÊNCIA DAS MULHERES METODISTAS À DITADURA CIVIL-MILITAR BRASILEIRA (1964-1985): UMA HISTÓRIA A SER CONTADA - LEITE, ANNA GABRIELA DE ARRUDA FELIX CERQUEIRA (2020)
During the Brazilian civil-military dictatorship, many women engaged in the struggle for a democratic country. Among the many unknown women who fought against the military regime, there are Methodist women, whose stories have been ignored until recently. This dissertation aimed to analyze the role of Methodist women in resisting the Military Dictatorship in Brazil (1964-1985). It was demonstrated what were the roles of these women in the struggle for democracy, having been “forgotten” by historiography about the dictatorship in the country. For this, the methodological path used was a bibliographic survey about what was written about the political agency of Protestant women, and also a documentary research carried out on official documents of the time, accessible in the archive of Deops (São Paulo State Department of Political and Social Order) Paulo), in the archives of the Brasil Nunca Mais digital project and also in the report of the National Truth Commission. In addition, semi-structured interviews were also conducted with former Protestant and political prisoners, according to the availability of access. It was verified what were the roles of these women in the fight against the military regime, evidencing the beginning of their political agency within their churches and later militancy in clandestine organizations. To bring their stories to the fore is to take them out of the unfair "deep silence" that imposed themselves on their struggle trajectories.